Rancang Bangun Sistem Aplikasi Ujian Akhir Sekolah Berbasis Jaringan Client Server Menggunakan Topologi Bus - Samudra, Yuda (Riau Jurnal Teknik Informatika, 2025)
The implementation of the final school exam at SMK Al Amanah has so far been carried out manually using paper, which causes various problems such as wasting time, risk of losing documents, and difficulties in the process of correction and recapitulation of grades. These problems encourage the need for the application of information technology in supporting learning evaluation activities. This research aims to design and build a client-server network-based school exam system with an efficient and affordable bus topology. This system was developed to increase the effectiveness of the exam and minimize errors in the assessment process. The methods used in this study include the stages of system design, software development using the PHP programming language and MySQL database, and the implementation of local networks using a simple and cost-effective bus topology. The system consists of a single main server that manages questions and exam result data, as well as several client computers that are used by students to work on questions simultaneously. The test results show that the system can run well in a local network environment with a bus topology, where students can access the questions and take the exam simultaneously without any significant obstacles. In addition, the time of correction and recap of values becomes faster and more accurate. With this system, the exam process at SMK Al Amanah becomes more efficient, safe, and organized.